The Relationship between Parental Style and Depressive Symptom among Secondary-School Students in Baghdad City, Iraq - Kalaf , Suhear H.; Mohammed, Qahtan Q. (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims to assess the patterns of parental style among adolescent students, in addition, to assess the level of depressive symptom among adolescent students, and to find out the significant relationship between parental style and depressive symptom among adolescent students finally to determine the significant differences in depressive symptom with socio-demographic characteristics of students such as: gender, scholastics stage, birth order, level of education for parents, economic level for parents .descriptive correlational design was used in the present study for the period from November 20th, 2019 to April 9th, 2020. The study was conducted on a systematic random sampling to select 18 schools from 65 secondary schools in Al-Karkh center and then sharing the questioner on social media (Facebook) to select 321 students. The present study showed that there are positive relationships between punitive and love with drawl parental style and depressive symptoms, in contrast, found a negative relationship between indicative parental style and depressive symptoms among secondary school students. We also found that more than half of the sample (60.1%) the mild symptom of depression and (30.2%) with a moderate symptom, in addition to (6%) with severe symptoms. the study concludes that the secondary school student affected psychologically with the style of rearing the parents used with them found no effect of demographic characteristics with the appearance of depressive symptom among secondary school students